Study of lactic acid bacteria and Enterobacteriaceae counts and fatty acids composition in a fermented product - Law, Fang Ling; Loh, Teck Chwen; Foo, Hooi Ling; Goh, Yong Meng; Idrus, Zulkifli (Veterinary Association Malaysia, 2006)
This study was conducted to study the characteristics of a fermented product (FP). An evaluation of measurements of consistency and repeatability on microbiological analyses, including lactic acid bacteria (LAB) and Enterobacteriaceae counts and fatty aids profiles was performed. Physico-chemical properties (pH, dry matter and ash, crude protein, crude fat and crude fibre) of FP were ascertained. The fermentation process was repeated three times under the same running conditions and using the same amounts of raw materials. The results indicated that the product obtained from the fermentation process increased the LAB population and decreased the Enterobacteriaceae populations after the fermentation process. The presence of essential fatty acids (linoleic acid 24%, linolenic acid 1.1 %, Eicosapentaenoic acid 3.6%, Docosapentaenoic acid 0.7%, and Docosahexaenoic acid 2.0%) and limeflavored aroma represents added value attributes to the product and it might have potential as an animal feed additive. Chemical determination showed a net decrease in pH to around 4.5. The dry matter, crude fibre, crude protein, crude fat and ash contents of the three batches of FP were similar. These results indicated that the quality of FP was consistent with repeatable preparation process.